Modelling Stiffness and Shear Strength of Compacted Subgrade Soils - Han, Zhong (Université d'Ottawa / University of Ottawa, 2016)
Compacted soils are frequently used as subgrade for pavements as well as commercial and residential buildings. The stiffness and shear strength properties of compacted soils, which are collectively denoted as Ω in this thesis, fluctuate with moisture content changes that result from the influence of environmental factors such as the evaporation and infiltration. For example, mechanistic pavement design methods require the information of resilient modulus (MR), which is the soil stiffness behavior under cyclic traffic loading, and its variation with respect to the soil moisture content determined from laboratory tests or estimation methods. Significant advances have been made during the last five decades to understand and model the variation of the Ω with respect to soil moisture content and soil suction (s) based on the principles of mechanics of unsaturated soils. There are a variety of models presently available in the literature relating the Ω to the s using different approaches. There are however uncertainties extending these models for predicting Ω - s relationships when they are used for a larger soil suction range. In addition, the good performance of these models are only valid for certain soil types for which they were developed and calibrated. Studies presented in this thesis are directed towards developing a unified methodology for modelling the relationship between the Ω and the s using limited while easy-to-obtain information. However, more emphasis has been focused on the MR - s relationships of pavement subgrade soils considering the need for the application of the mechanistic pavement design methods in Canada. The following studies have been conducted: (i) State-of-the-art review on existing equations in the literature for the MR - s relationships is summarized. A comparison study is followed to discuss the strengths and limitations of these equations; (ii) A unified methodology for modelling the Ω - s relationships is proposed. Experimental data on 25 different soils are used to verify the proposed unified methodology. The investigations are applied on small strain shear modulus, elastic modulus, and peak and critical shear strength. Good predictions are achieved for all of the investigated soils; (iii) Performance of the proposed methodology is examined for the MR - s relationships using experimental data of 11 subgrade soils. Reasonably good predictions are achieved for all of the subgrade soils; (iv) Extensive experimental investigations are conducted on the MR - s relationships for several subgrade soils collected from various regions in Canada. Experimental results suggest non-linear variation in the MR with respect to s, moisture content and the external stress. The measured results are modelled using the proposed methodology with adequate success; (v) Additional experimental investigations are performed to determine the variation of the elastic modulus (E) and unconfined compression strength (qu) with the s and the gravimetric moisture content (w) for several Canadian subgrade soils. An approach, which is developed extending the proposed unified methodology, is used to normalize the measured MR - w, E - w and qu - w relationships. It is shown that the normalized MR - w, E - w and qu - w relationships exhibit remarkable similarity and can be well described using the proposed approach. Such similarity in the normalized Ω - moisture content relationships are also corroborated using the experimental data on several other soils reported in the literature. The proposed unified methodology alleviates the need for the determination of the Ω - s relationships which requires elaborate testing equipment that needs the supervision of trained personnel and is also time-consuming and expensive. In addition, experimental programs in this thesis provide detailed experimental data on the MR, E, qu, and soil-water characteristic curves of Canadian subgrade soils. These data will be helpful for the better understanding of the hydro-mechanical behavior of the Canadian subgrade soils and for the implementation of the mechanistic pavement design method in Canada. The simple tools presented in this thesis are promising and encouraging for implementing the mechanics of unsaturated soils into conventional geotechnical engineering practice.
Keywords: Stiffness; Shear strength; Unsaturated soil; Prediction; Pavement subgrade; Resilient modulus